Debating Turkish health reform - Kartal, Ayşecan. (Thesis (Ph.D.) - Bogazici University. Atatürk Institute for Modern Turkish History, 2019., 2019)
This dissertation is a study of the political debate that got generated around health reform in Turkey between 2002 and 2011, which corresponds to the formative period for the debate. Through a close examination of both the proreform and anti-reform discourse on health, it shows how a technical issue such as health care became a primary ground of political debate, contestation and polarization in the Turkey of early 2000s. More specifically, the AKP’s pro-reform discourse and the progovernment media presented health care providers and health care receivers as opposing groups and positioned the AKP as the protector of health care receivers. This pro-reform discourse emphasized the universalist trend in the reform that abolished the inegalitarian structure of the pre-existing health system and extended coverage. On the other side of the political debate, opponents of the reform, mainly the TTB (Turkish Medical Association), highlighted the neoliberal aspects of the reform. However, the oppositional discourse did not receive wide support as it was formulated when the short term benefits introduced by the reform were still in effect.
Keywords: Health care reform -- Turkey.; Medical policy -- Turkey.